Species and biotype distribution of thermotolerant Campylobacters in animal reservoirs in Southern Chile - Heriberto Fernandez (Revista do Instituto de Medicina Tropical de São Paulo, 1988)
The prevalence of thermotolerant Campylobacters in mammals and birds from Southern Chile was determined. Campylobacters were isolated from 46.3% of the animals studied being C. jejuni biotipe 1 the most frequent (25.7%) followed by C. coli (17.4%) and C. jejuni biotipe 2 (3.2%).